Onuphidae (Annelida, Polychaeta) from Japan, excluding the genus Onuphis. - Imajima, Minoru (National Science Museum Monographs, 1999)
Onuphid polychaetes, excluding the genus Onuphis, are recorded from Japanese waters. Twenty-eight species, including 18 endemic species (64%), representing nine genera, are recognized and the descriptions of their morphology and keys to the 28 species are presented. Specimens examined for this study came from depths ranging from intertidal to abyssal and from Hokkaido in the north to Amami-Oshima in the south. Three genera, Notonuphis, Paradiopatra and Epidiopatra, are reported for the first time from Japanese waters. Ten new species are described as follows: Nothria oblonga, Nothria paxtonae, Anchinothria tosaensis, Hyalinoecia acuta, Hyalinoecia papillata, Notonuphis abyssalis, Paradiopatra crassa, Paradiopatra simplex, Paradiopatra unica, Paradiopatra okai. Five species, Anchinothria crassisetosa, Hyalinoecia abranchiata, Kinbergonuphis bathyalis, Kinbergonuphis proalopus and Rhamphobrachium (Spinigerium) hutchingsae are newly reported from Japan. About half of the 28 species are widely distributed in Japanese waters, and those with wide latitudinal ranges also have wide vertical ranges.
AnnelidaBase